Awareness, use and understanding of nutrition labels among adults from five countries: Findings from the 2018–2020 International Food Policy Study. (1st January 2023) - Acton, Rachel B.; Rynard, Vicki L.; Adams, Jean; Bhawra, Jasmin; Cameron, Adrian J.; Contreras-Manzano, Alejandra; Davis, Rachel E.; Jáuregui, Alejandra; Sacks, Gary; Thrasher, James F.; Vanderlee, Lana; White, Christine M.; et al.
Abstract: Few studies have compared the effects of different front-of-package label (FOPL) systems in the 'real world'. This study assessed adults' awareness, use and understanding of nutrition facts labels (NFLs) and nationally implemented FOPLs such as Health Star Ratings (HSR), Traffic lights, and Guideline Daily Amounts (GDAs) in five countries, including before and after implementation of Mexico's warning FOPLs in 2020. Data were from the International Food Policy Study, an annual repeat cross-sectional study conducted in 2018-2020 among adults (N=64, 032) in Australia, Canada, Mexico, the UK and the US. Self-reported awareness, use, and understanding of NFLs (in all five countries) and FOPLs (in Australia, Mexico, and UK) were assessed over time, between countries, and between NFLs and FOPLs. Most respondents in all countries reported seeing their country's NFLs ( awareness ) 'often' or 'all the time' across all three years, with one third to half of respondents using NFLs 'often' or 'all the time' (Australia: 43-45%; Canada: 47-50%; Mexico: 36-39%; UK: 32-34%; US: 47-49%), and approximately one half to two thirds finding NFLs 'easy' or 'very easy to understand' (56-57%; 67-69%; 51-54%; 48-51%; 70-71%). In 2020, awareness, use and self-reported understanding of the Warning FOPLs in Mexico were highest among all countries with a FOPL (p<0.001), whereas awareness and use were lowest for Australia's HSR (p<0.001). In countries with FOPLs, self-reported understanding was higher for FOPLs than NFLs, except for the GDA FOPL in Mexico. Only modest changes were observed over time. Warning FOPLs were associated with greater levels of self-reported awareness, use and understanding among adults compared to NFLs and GDA-based FOPLs. FOPLs implemented on a voluntary basis, such as Australia's HSR, may be less likely to be seen and used.